Dynamics of a fin driven boat - modeling and simulation - H. T. Tran; S. Bikowski; C. D. Wolf; P. Maiber (Vietnam Journal of Mechanics, 2003)
In this paper the motion of a small sport boat running on a lake is simulated using alaska tools when the external forces and torques from water and excitation force from a person are applied. Using the results from measurements we have done some validations.